The emptiness of our hands : 47 days on the streets - Cole-Dai, Phyllis, 1962-; Murray, James (Bell Sounds Books, 2018)
"For forty-seven days in 1999, Phyllis Cole-Dai and James Murray lived by choice on the streets of Columbus, Ohio, the nation's fifteenth-largest city. They went to the streets to practice presence: to offer nonjudgmental attention and compassion to everyone they met, especially the chronically homeless, who are so often ignored, scorned, abused, or shunned. 'The Emptiness of Our Hands,' now in its third edition, is a meditative chronicle of their experiences, including nearly thirty black and white photographs, most shot by James using crude pinhole cameras he constructed from trash. This book will thrust you out the door of your comfortable home, straight into the unknown. Who might you be when you come back?" -- page [4] of cover
Includes bibliographical references.
Keywords: Homeless persons -- Ohio -- Columbus; Homelessness -- Religious aspects; Homeless persons; Homelessness -- Religious aspects; Ohio; Ohio -- Columbus